Sosialisasi Pembuatan Pestisida Nabati Kelompok Wanita Tani RW 14 Kelurahan Gedog - Eva Tri Agustin; Siti Salzabila Faizaroh Aizy; Noni Cornelasari; Mu'tasim Billah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Kelompok Wanita Tani is a group of farmers which consists mostly of women such as housewives and farmers' wives who carry out their business in agriculture. One of Kelompok Wanita Tani, Kelompok Wanita Tani RW 14 where they mostly produce commodity that is attacked by aphids. Maintenance efforts that have been carried out so far are by spraying chemical pesticides. The use of chemical pesticides regularly can result in a negative effect, therefore innovation is needed in the form of organic pesticides. Natural sources such as plants are the main ingredient of organic pesticides. Kelompok KKN-T MBKM 138 carry out community service by providing socialization on the making of organic pesticides. The methods of implementing the community service are starting from planning, practice and experimentation of making organic pesticides, and implementation (socialization, demonstration, and handover of the organic pesticides to Kelompok Wanita Tani). The making and socialization of organic pesticides are already been done on Kelompok Wanita Tani RW 14. The making of organic pesticides has been observed for 2 weeks and obtained the results that it is effective to be carried out on eggplant plants affected by aphids. After achieving a successful result of the observations that have been made, a socialization is held to add insight into the Kelompok Wanita Tani RW 14.